Fundamentalism: a Religious Cognitive Bias? A Philosophical Discourse of Religious Fundamentalism - Eduardus Lemanto (RUDN Journal of Philosophy, 2023)
Fundamentalism has been widely reckoned as one among many other watchful social phenomena currently. There are two general approaches to it. The first is from those who perceive fundamentalism as a movement of militant piety found almost in any religion, and therefore fundamentalism cannot necessarily be identified with a violent movement. The second is from those who categorize fundamentalism as a political movement with an objective of worldly power, and therefore it is susceptible to turning into a violent movement. In investigating the two views closely, I attempt to put forward a couple of hypothetical inquiries. Is fundamentalism a common phenomenon and common feature found in almost any religion? The answer is yes. Is fundamentalism identical to violent movement? The answer is no. Is fundamentalism then impossibly and utterly unrelated to violent movements? The answer is no. If fundamentalism is unidentical with violent movements but not a few fundamentalists can also turn to be perpetrators of what is called religious violence or violence in the name of religion, then what arguments can be set forth to ensure that fundamentalism cannot be overlooked anymore as one among many other major social problems of our age? This article aims to examine fundamentalism through epistemological and axiological criticism, and to investigate that to a certain range fundamentalism is a form of religious cognitive and behavioral bias, and both as a militant piety and as a political movement fundamentalism should at best be approached from their interplayed relation.